Reconstruction of the sedimentary structure and subsidence of the Congo Basin using geophysical data and numerical models - Maddaloni F.; Delvaux D.; Munch J.; Tesauro M.; Gerya T.; Braitenberg C. (EGU General Assembly 2019, 2019)
The Congo basin (CB) occupies a large part of the Congo Craton (1.2 million km2) covering approximately 10% of the continent. It contains up to 9 km of sedimentary rocks from Mesozoic until Quaternary age. The formtion of the CB started with a rifting phase during the amalgamation of the Rodinia supercontinent at ~ 1.2 Gyr and the main episodes of subsidence occurred during the following post-rift phases in the Neoproterozoic and Paleozoic, separated by late Pan-African compressional inversion [1]. After a new compressional inversion at the end of the Permian, sedimentation resumed during the Mesozoic; since Cretaceous, the CB has been subjected to an intraplate compressional settng due to ridge-push forces related to the spreading of the South Atlantic Ocean [1]. In this study we first interpreted the seismic reflection profiles and well logs data located inside the central area of the CB, to reconstruct the stratigraphy/tectonic evolution of the basin. Afterwards, we compared geological and geographycal information to estimate the velocity, density, thickness of the sedimentary layers and the depth of the lithostratigraphic units. The results have been used as input parameters for a 3D numerical simulations, testing the main mechanisms of formation and evolution of the CB. To study this, we used the 3D thermomechanical code I3ELVIS [2] to simulate the initial rift phases. For the first experiments, we assumed that the Congo craton is made of four blocs of Archean age. We applied extensional stresses in the N-S and E-W directions (orthogonal stresses) [1] to test the hypothesis of the formation of a multi extensional rift in a cratonic area. The results of these first numerical experiments show that the deformation is localized in the central part of the CB. [1] De Wit, M.J., Stankiewicz, J., Reeves, C.V., (2008), Restoring Pan-African-Brasiliano connections: more Gondwana control, less Trans Atlantic corruption, 294, 10.1144/SP294.20, Geological Society, London, Special publications. [2] Gerya, T., ...